The Dirac Equation in Geometric Quantization - Bona, Andrej (Birkhauser Verlag AG, 2003)
The coadjoint orbit of the restricted Poincaré group corresponding to a mass m and spin 1/2 is described. The orbit is quantized using the geometric quantization. To include the discrete symmetries, one has to induce the irreducible representation of the restricted Poincaré group obtained by the quantization procedure to the full Poincaré group. The new representation is reducible and the reduction to an irreducible representation corresponds to the Dirac equation.